Relationship between Chinese middle-aged and old couples' Confucian coping thinking and marital quality - Fan, Zhiguang; Wu, Hanwei; Tao, Min; Chen, Lei (Frontiers in Public Health, 2022)
Objective: Drawing on the actor-partner interdependence model (APIM), the present study investigated the relationship between Chinese middle-aged and old couples’ Confucian coping thinking and their marital quality in hope to provide theoretical basis for ameliorating marital quality. Methods: With 744 middle-aged and old couples as participants, the Confucian Coping Questionnaire (CCQ) and the Quality of Marriage Index (QMI) were employed to probe the relationship between responsibility thinking (RT), pro-setback thinking (PT), fate thinking (FT) and marital quality. Results: Husbands’ and wives’ scores in RT and PT had significantly positive correlations with their own and their spouses’ scores in marital quality respectively, and husbands’ and wives’ scores in FT had significantly negative correlations with their own and their spouses’ marital quality respectively. Husbands’ RT, PT and FT had a significant actor effect. Husbands’ RT and FT had a significant partner effect. Wives’ RT, PT and FT had a significant actor effect. Wives’ RT and PT had a significant partner effect. Conclusion: From the perspective of dyadic relationship, it was found in the present study that RT and PT had a positive impact on marital quality, while FT had a negative impact on marital quality.